Multicriteria Decision Analysis for Updating of Quality Indicators for Inflammatory Bowel Disease Comprehensive Care Units in Spain. (11th May 2022) - Calvet, Xavier; Panés, Julián; Gallardo-Escudero, Javier; de la Cuadra-Grande, Alberto; Bartolomé, Elena; Marín, Laura; de la Portilla, Fernando; Navarro-Correal, Ester; Gutiérrez, Ana; Nos, Pilar; Serrano, Ruth; Casado, Miguel Ángel; et al.
Abstract: Background and Aims: Management of inflammatory bowel disease [IBD] is complex and IBD Comprehensive Care Units [ICCUs] facilitate the delivery of quality care to IBD patients. The objective of this study was to update the existing set of quality indicators [QIs] for ICCUs, based on a nationwide quality certification programme carried out in Spain, from a multi-stakeholder perspective and using multicriteria decision analysis [MCDA] methodology. Methods: An MCDA comprising three different phases was conducted. In phase 1, a systematic literature review was performed, and after validation by a scientific committee comprising 11 experts, a preliminary set of QIs was developed. In phase 2, a larger group of 49 experts determined the relevance and relative importance of each QI by prioritising and weighing the preliminary set. Finally in phase 3, the scientific committee reviewed the results and made a final selection via a deliberative process. Results: The final set comprised 67 QIs, classified as Structure [23 QIs], Process [35 QIs] and Outcome [9 QIs], which were ranked according to their relative importance. Multidisciplinary management was the most important requirement in ICCUs, followed by continuity of care, standardisation of clinical care and, especially, the incorporation of patients' reported outcomes. Conclusions: This updated set of QIs comprises a weighted and prioritised set of items that represent the essential minimum of criteria for ensuring appropriate quality of care in the management of IBD patients.